Kajian Visual Desain Karakter Kancil pada Animasi 3D “Kancil” - Lionardi, Angelia (Visualita Jurnal Online Desain Komunikasi Visual, 2022)
Fairy tales are one of the cultures in Indonesia which are now starting to be preserved by adapting them to a more modern form. Fairy tales are not only adapted into songs or in the form of writings/books of fairy tales but also into animated media, both 2D and 3D. One of the song which inspired by a fairytale that has undergone a process of adaptation to 3D animation media is the Kancil fairy tale. The author is interested in observing how the adaptation process for designing the Kancil character is carried out. In this study, the author will also conduct a visual study of the design of the mouse deer character in the Kancil animated film produced by Visinema Pictures in collaboration with Afterlab Studio. The research will be conducted using a qualitative descriptive method. Data was collected through literature studies and interviews with the designer of the Kancil character. The results of this study can be a reference for other designers who want to carry out the process of adapting characters from fairy tales into more modern media particularly in 3D animation.